Proyecto de factibilidad para la implementación de una Empresa productora y comercializadora de chocolates en el cantón Shushufindi, para el año 2015 - Llano Tutillo, Mayra Susana (2016)
The investigative work is since of great importance it was developed with the purpose of taking advantage of the matter it prevails taken place in the canton Shushufindi, like it is the cocoa, and for the great demand that it exists for the chocolate. This way contributing to the socioeconomic development of the town, generating sources of direct and indirect employment, improving the economy of their homes and of the sector in general. To treat the present he/she fears it was used the methods: scientific, inductive, deductive, analytic, which allowed to determine the existent problem in the mean, as well as the investment opportunities thanks to the resources and demand exist in the town. For the Study of Market you application 500 surveys to the population of the canton Shushufindi; having 379 surveys been worth that they were developed the economically active population of the canton; which allowed to determine a potential demand of 27.393 people; of which 47,43% consumes chocolate in bar, giving like real demand 12.992 people, of where 89,43% is the possible clients to the moment that the project is implemented, giving like effective demand of 11.619 people, with an average of consumption of 7,5 monthly bars of chocolate and of 90 annual bars that when multiplying for the effective demand, he/she gave as a result 1.045.718 bars of chocolate. The offer of the product was determined, for that which was carried out a survey to 371 owners of stores, cellars, distribuidoras, among other, of which 73,05% of the establishments sells this product, with a total sale of 505.494 bars of annual chocolate; when relating with the effective demand he/she gave as a result 540.224 bars of chocolate in the unsatisfied demand. By means of the technical study an installed capacity could settle down, analyzing the capacity of the machinery, that which allowed to determine that the machinery extractora of liquor has a capacity to produce the matter for 728.000 bars of chocolate of 25g. it corresponds to 99,97% of the unsatisfied demand, additionally it was possible to identify the micro and macro good localization for the location of the project, and reaching the conclusion that the company will settle in the cantonal head of Shushufindi, in the neighborhood Las Vegas, in the street Jumandy among Oriental and Av. Napo, the same one that will be suitable for the development of the activities; since this sector has the basic necessary services, as well as he/she has access to the sector where the matter is cultivated it prevails and it is inside the existent market for this product. In the engineering of the project, the physical infrastructure and the distribution of the plant were designed where consist all the departments of the company that he/she has a global measure 15 meters wide for 11 meters long, what corresponds at 165m2. The process diagram was developed for the production of the chocolate, from the cleaning of the cocoa until the packing of the finished product; It was analyzed, the necessary requirements for the operation of the company, like they are the machinery, the tools, the furniture, especially the matter prevails necessary for the elaboration of the product. In the administrative study it was determined that the company is constituted as Limited Company, with the name of: Amazon Chocolatera, which consists of three partners that will have the same number of actions each one. The Administrative structure the one was elaborated which consists of the structural, functional flowcharts and posicional; for each one of the positions the manual of functions was elaborated. By means of the economic study you to determine that for the installation of the project an investment of USD $ is needed 69.971,50 dollars of the United States of America the same one that 49,98% will be financed by own capital and 50,02 remaining% by means of a financial institution with an interest rate of 12%, the production cost for the first year is of USD $ 143.103,68 dollars of the United States of America, with an entrance for sales of USD $ 203.840,00 dollars of the United States of America with an utility liquidate of USD $ 36.241,36 dollars of the United States of America and a flow of effective of 32.198,31 dollars of the United States of America. When carrying out the financial evaluation you could determine what after having recovered the investment one will have a benefit of USD $ 179.479,76 dollars of the United States of America with an internal rate of return of 27,84% that is bigger to the discount rate; of each invested dollar one will have USD $ 0,43 cents of dollar of the United States of America in utility; the period of capital recovery is of 2 years, 3 months and 10 days; if the costs are increased until 9,59% or the revenues diminish 8,04% the project it is not sensitive; for what you can conclude that the project is feasible the indicators demonstrate financially since this way it. For what you concludes that the project should be implemented since with he/she will bring it non alone economic if not also social benefits.